PENERAPAN AKAD MUDHARABAH DAN MUSYARAKAH DI PASAR MODAL SYARIAH INDONESIA - Retno Dyah Pekerti; Rizky Ridwan (LP2M Universitas Perjuangan Tasikmalaya, 2022)
The Covid-19 pandemic has had many impacts on people in Indonesia, one of which is in terms of the economy. However, at the same time, the Indonesian capital market actually experienced an increase in the number of investors by 87.59 percent until December 2021. From this increase, it is expected that all users in the capital market, especially in the Islamic capital market, will know the principles and contracts made to transact in the Islamic capital market. The results of the study explain that mudharabah and musyarakah contracts can be used in transactions in the capital market with the condition that they must comply with sharia principles and each party must know their rights and obligations. This study uses descriptive qualitative methods with data collection techniques by library research (library study) where the authors collect data from books, articles, journals, internet sources and magazines related to the research. Keywords: Sharia Capital Market, Mudharabah Contract, Musyarakah Contract